Kefahaman Pelajar dalam Proses Rawatan Air Sisa Bagi Kursus DCC5152 dalam Kalangan Pelajar DKA, Politeknik Sultan Mizan Zainal Abidin - Siti Khatijah Mohamad; Nazmiah Nawi (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2023)
This study was conducted to enhance students' understanding of wastewater treatment for DCC5152 courses among DKA, PSMZA students. The respondents involved were 25, Semester 4 Civil Engineering Diploma Program (DKA) Session June 2017, Civil Engineering Department Sultan Mizan Zainal Abidin Polytechnic. The objective of this action study is to enhance students 'understanding through the identification of students' interest in furthering the topic of wastewater treatment, and identifying obstacles faced by students in the process of learning wastewater treatment for the DCC5152 course. The research method used is quantitative and qualitative study method. Data collection was conducted through questionnaires and interview sessions. The results of this study showed that the respondents had a low percentage of understanding on the topic of wastewater treatment by 15.5%. While 71% of respondents showed high interest in the topic of wastewater treatment and the main obstacle students in mastering wastewater treatment topics were 80% English reference source. The execution of the action is completed within 3 weeks. The action plan was an emphasis on past final exam questions, accessing videos related to the waste water treatment process and providing mind map notes. The result showed that there was an increase in the students' understanding on the topic of wastewater treatment as much as 68% from the knowledge aspect, 72% for the treatment process and 60% from the aspect of treatment method to get excellent results. In conclusion the study has a positive impact and may be suggested for further research.